E.E. Green’s collection of scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) in The Natural History Museum, London, U.K. - Williams, D.j. (Zootaxa, 2017)
In 1940, E.E. Green’s collection of scale insects, consisting of 6505 microscope slides and 2172 boxes of dry material, was donated to the The Natural History Museum, London, U.K. (then the British Museum (Natural History)). Green was a tea and coffee planter in Sri Lanka, and later became Government Agricultural Entomologist there before retiring to England in 1913. He continued to work on scale insects and became one of the foremost scale insect specialists at the time. His collection includes most of the species he described as new, but is also important because it contains authentic material sent to Green by other contemporary workers on scale insects.                         The collection is listed as it was when originally donated, firstly giving the names of species that Green recognised at the time, followed by the number of microscope slides, followed by numbers of developmental stages in the material; lastly is provided the current name of each species. The list is divided into the 31 extant families represented in Green’s collection.